2015
DOI: 10.1016/j.fishres.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Use of state-space population dynamics models in hypothesis testing: advantages over simple log-linear regressions for modeling survival, illustrated with application to longfin smelt (Spirinchus thaleichthys)

Abstract: a b s t r a c tFactors impacting the survival of individuals between two life stages have traditionally been evaluated using log-linear regression of the ratio of abundance estimates for the two stages. These analyses require simplifying assumptions that may impact the results of hypothesis tests and subsequent conclusions about the factors impacting survival. Modern statistical methods can reduce the dependence of analyses on these simplifying assumptions. State-space models and the related concept of random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…Stock assessments are usually applied to harvested fishes, particularly those in marine ecosystems. Although the Longfin Smelt is not targeted for harvest in the SFE, it is nonetheless useful to construct explicit spawnerrecruit relationships so as to evaluate different conceptual models of Longfin Smelt recruitment (see also Maunder et al 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stock assessments are usually applied to harvested fishes, particularly those in marine ecosystems. Although the Longfin Smelt is not targeted for harvest in the SFE, it is nonetheless useful to construct explicit spawnerrecruit relationships so as to evaluate different conceptual models of Longfin Smelt recruitment (see also Maunder et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The Longfin Smelt is also one of several SFE fishes that have shown a strong and persistent association between juvenile production and the freshwater flow variation experienced early in the life cycle (Stevens and Miller 1983;Jassby et al 1995;Kimmerer 2002b;Rosenfield and Baxter 2007;Thomson et al 2010;Maunder et al 2015). However, little attention has been given to whether and how freshwater flow rates might affect production of Longfin Smelt beyond the first year of life.…”
Section: Longfin Smelt Population Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary analyses considered Gompertz State-Space Population Models (Dennis et al, 2006;Knape and de Valpine, 2012) which estimate both process and observer error (Maunder et al, 2015). However, the models were unable to reliably estimate both error terms.…”
Section: Population Modelsmentioning
confidence: 99%
“…However, the models were unable to reliably estimate both error terms. As the observer error was estimated to be smaller than the process error and because ignoring process error can bias Akaike's Information Criterion 4/43 based tests towards incorrectly accepting covariates (Maunder et al, 2015), we followed Garton et al (2011) in assuming no observer error. The preliminary analyses indicated that fixing the observer error at zero had little effect on the results.…”
Section: Population Modelsmentioning
confidence: 99%